(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article talks about the importance of chemicals in the development of plants. Also, the importance of phosphorus for plants, its amount and forms in the soil are highlighted.